Effect of Training Program Regarding Occupational Health Hazards on Nurse Interns’ Knowledge and Practice (Medico Legal Update, 2021)
Background: Nurse Interns face a wide range of hazards in hospitals including needle stick injuries, backinjuries, latex allergy, violence, and stress.The goal of this study: Identify the impact of training program regarding occupational health hazardson nurse interns’ knowledge, practice and attitude through: assessing nurse interns’ knowledge regardingoccupational health hazards before and after the program, assessing nurse interns’ practice regarding ofoccupational health hazards before and after the program,assessing nurse interns’ attitude regarding ofoccupational health hazards before and after the program, designing and implementing the training programand measuring the effect of training program regarding occupational health hazards on nurse interns’knowledge and practice.Design: Quisi- experimental research design.Subject: The study was conducted at four hospitals affiliated to Ain Shams University. The subjects of thisinvestigation included 91 nurse interns.Tools of data collection: Data were collected by using four tools namely: Needs assessment sheet, Self -administered Questionnaire, Observation Checklist, and attitude scale.Results: Highly significant differences of total occupational health hazards knowledge among nurse internsthroughout program phases was observed. Nurse interns’ total practice regarding occupational health hazardswas markedly increased throughout program phases. Highly significant difference in total attitude towardsprotection from hazards throughout the program phases was noticed.Conclusion: Implementation of the training program led to significant improvements in nurse interns’knowledge, practice, and attitude regarding occupational health hazards.Recommendations: providing training program for nurse interns about occupational hazards andespecially on protective measures, development and dissemination of policies and guidelines of safetypractices, evaluation sheet of the nurse interns should include items related to occupational health hazardsand compliance ways of protection, and further investigation might include factors affect reporting ofoccupational hazards.